"Kiss My Donkey!" or Raising the Level of Authentic Communication in My Core French Classroom - Jan Claes (Networks: An Online Journal for Teacher Research, 2003)
The way I see it, teacher action research found me rather than my finding it. In April of 2002, I attended the Quebec Conference on Teacher Action Research in Montreal as an observer. Having absolutely no prior experience with the concept, I was at first completely overwhelmed by the puzzling new vocabulary and by the obvious passion of the participants. Then, about halfway through the second day, I suddenly understood. It felt as if an internal dam were breaking and I began to engage in conversation after exciting conversation about the phenomenal power of this approach.